Cytokine gene polymorphisms in Pigeon Breeder’s Disease expression - Freitas, Cláudia; Lima, Bruno; Martins, Natália; Melo, Natália; Mota, Patricia; Novais-Bastos, Helder; Alves, Helena; Sokhatska, Oksana; Delgado, Luís; Morais, António (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2020)
Background: Exaggerated immunological response to repeated inhalation of organic or chemical dusts may lead to Hypersensitivity Pneumonitis among sensitized individuals. Only a few exposed individuals became ill and disease expression pattern is highly variable which suggest that genetic factors may play a role. Objective: To investigate interferon (IFN)-γ, tumour necrosis factor (TNF)-α, interleukin (IL)-6, transforming growth factor (TGF)-ß, and IL-10 gene polymorphisms in a cohort of pigeon breeder’s disease (PBD) patients in comparison with asymptomatic exposed controls and the association with different patterns of disease. Methods: We evaluated 40 PBD patients and 70 exposed controls. IFN-γ, TNF-α, IL-6, TGF-ß, and IL-10 polymorphisms were determined by polymerase chain reaction–sequence specific primer amplification. Results: Polymorphism analysis of IFN-γ, TNF-α, IL-6, TGF-ß, and IL-10 genotypes and allele frequencies showed no differences between patients and controls. IFN-γ T/T genotype frequency was increased among patients with chronic presentation (RR=2.33, p=0.047) compared with those with acute/subacute presentation. Also, chronic presenting patients had an increased frequency of IFN-γ T allele (50% vs 22.5%, RR=1.76, p=0.011). No differences were found in TNF-α, IL-6, TGF-ß, and IL-10 genotypes neither allelic frequencies between both groups of patients. IL-6 C/C genotype was more frequent in patients who showed chronic evolution (RR=2.54, p=0.017), when comparing with patients with disease resolution. Conclusion: IFN-γ T/T and the IL-6 C/C genotypes seem to play a role in HP expression, as their frequencies are increased in chronic presentations or in those with chronic evolution one year after the initial diagnosis, respectively.